Implementation of intervention programs specifically tailored for patients with cognitive impairment as comorbidity in early rehabilitation during acute hospitalization: an umbrella and scoping review - Ullrich, Phoebe; Dutzi, Ilona; Buchner, Theresa; Werner, Christian; Bongartz, Martin; Bauer, Jürgen M.; Hauer, Klaus (Geriatric nursing, 2025)
Introduction - Cognitive impairment (CI) is common among older hospitalized patients, posing risks for adverse events. However, the extent to which early rehabilitation interventions address CI needs is unclear. This umbrella and scoping review evaluates CI consideration in such interventions during acute hospitalization. - Material and Methods - Systematic reviews on early rehabilitation interventions for older patients were screened. Inclusion criteria encompassed CI mention in titles/objectives, patient assessment/description, inclusion of CI patients, (sub-) analyses by cognitive status, and tailored interventions. - Results - Of 199 studies, only 3% addressed CI in titles/objectives, 68% assessed cognitive status, and 42% lacked CI patient information. Only 4% targeted CI patients, 55% included mixed populations. In 12% of studies, CI patient results were reported, 8% adjusted analyses for CI. Only 5% tailored interventions for CI. - Discussion - Despite high prevalence, CI patients are largely overlooked in early rehabilitation. Future studies should consider CI in assessment, description, analysis, and intervention design.